Policing the urban environment in premodern Europe - Rawcliffe, Carole, 1946-; Weeda, Claire (Amsterdam University Press, 2019)
Tapping into a combination of court documents, urban statutes, material artefacts, health guides and treatises, 'Policing the Urban Environment in Premodern Europe' offers a unique perspective on how premodern public authorities tried to create a clean, healthy environment. Overturning many preconceptions about medieval dirt and squalor, it presents the most outstanding recent scholarship on how public health norms were enforced in the judicial, religious and socio-cultural sphere before the advent of modern medicine and the nation-state, crossing geographical and linguistic boundaries and engaging with factors such as spiritual purity, civic pride and good neighbourliness.